Molecular Profiling of Odontogenic Tumors - Pilot Study - Gültekin Sibel Elif; Sengüven Burcu; Aziz Reemitcha; Heydt Carina; Buettner Reinhard (Balkan Stomatological Society, 2017)
Background/Aim: In the pathogenesis of odontogenic tumors which arise from the rests of the dental apparatus in the jaw, several molecular pathways have been shown to play critical roles such as genetic alterations in the hedgehog, BRAF/Ras/MAPK, epidermal growth factor receptor. Next generation genomic sequencing has identified gene mutations in many different tumors. Materials and Methods: Here we report four types of odontogenic tumor including six cases in which five had mutation according to next generation sequencing analysis from archival paraffin blocks that diagnosed previously as ameloblastoma (solid), amloblastoma (unicystic-mural), ameloblastic fibroma, squamous odontogenic tumor, and adenomatoid odontogenic tumor. Results: All ameloblastomatic tumors were shown BRAF mutation and adenomatoid odontogenic tumors were KRAS mutation. Conclusion: This evidence may highlight the poorly understood pathogenesis of odontogenic tumors. Further comparisons need to be made with other benign and malignant odontogenic tumors so that unique odontogenic features may be found.